2014
DOI: 10.1136/thoraxjnl-2014-206260.19
|View full text |Cite
|
Sign up to set email alerts
|

S13 Incidence And Risk Factors For The Development Of Hospital Acquired Pneumonia In Older Hospitalised Patients

Abstract: Method Up to 140 EU sites will enrol 1000 patients. Safety data are recorded at routine clinic visits for 2 years. Adverse drug reactions (ADR: a noxious, unintended drug response at therapeutic doses) and serious ADRs (SADR: ADRs that are lifethreatening; cause death, disability, congenital anomaly; require hospitalisation or an intervention to prevent permanent impairment) are collected. Results Data from 530 patients enrolled by 68 sites in 7 countries are included. Age was 69 ± 8.8 years (mean ± SD); IPF d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…23 According to Burton et al, mortality rate was 29% in patients with confirmed HAP, and 19% in patients with suspected HAP. 24 In the present study, only PSI had the prognostic power to predict 30 day mortality and the use of mechanical ventilation in the HAP group. Neither CURB-65 nor SMART-COP had the prognostic power to predict 30 day mortality or the use of mechanical ventilation in the HAP group.…”
Section: Discussionmentioning
confidence: 55%
“…23 According to Burton et al, mortality rate was 29% in patients with confirmed HAP, and 19% in patients with suspected HAP. 24 In the present study, only PSI had the prognostic power to predict 30 day mortality and the use of mechanical ventilation in the HAP group. Neither CURB-65 nor SMART-COP had the prognostic power to predict 30 day mortality or the use of mechanical ventilation in the HAP group.…”
Section: Discussionmentioning
confidence: 55%
“…On the other hand, we found that distinct adverse outcomes, such as death, might be associated with selected conditions, such as cancer or diseases other than immune-mediated disorders, while nosocomial infections might selectively cluster with upper gastrointestinal disorders. These data indicate that, besides quantitative changes in hospital workforce, improvements are also needed in current practice, possibly with the adoption of personalised strategies to address individual-or group-specific determinants of complexity and, eventually, of morbidity and mortality [26] through multidisciplinary teams [27][28][29]. In particular, patients with vulnerability factors for airborne and bloodborne infections such as those with impaired ability to protect their airways, receiving oxygen support or undergoing invasive procedures may require dedicated assistance paths to minimise the risks of nosocomial infections [26,30].…”
Section: Discussionmentioning
confidence: 99%
“…One of the major findings of the guidelines was an almost complete lack of UK data on the management of hospital-acquired pneumonia (HAP), and so it was refreshing to see a study by Burton et al describing the incidence and risk factors for HAP in a large cohort of 1302 patients. Perhaps not surprisingly, aspiration was a major risk factor and mortality was high 30. HAP is a key area of unmet need in respiratory medicine.…”
Section: Respiratory Infectionsmentioning
confidence: 99%